Knowledge of the Genetic Information Nondiscrimination act among individuals affected by Huntington disease. (20th December 2012) - Dorsey, ER; Darwin, KC; Nichols, PE; Kwok, JH; Bennet, C; Rosenthal, LS; Bombard, Y; Shoulson, I; Oster, E
Abstract : The Genetic Information Nondiscrimination Act (GINA) of 2008 was the first US legislation to address genetic discrimination. We sought to assess understanding of GINA among individuals affected by the autosomal dominant condition, Huntington disease (HD). We conducted a cross‐sectional survey of individuals with varying risk of HD to assess their familiarity with GINA. As a control, individuals were surveyed about their familiarity with the Health Insurance Portability and Accountability Act (HIPAA). Those who reported familiarity with GINA were asked about their knowledge of specific provisions of the legislation. The survey was offered to 776 participants and completed by 410 (response rate 53%). Respondents across all groups were less familiar with GINA (41% slightly, somewhat, or very familiar) than with HIPAA (65%; p < 0.0001). Of individuals with or at risk for HD who reported some familiarity with GINA, less than half correctly identified GINA's protections, and less than 15% correctly identified its limitations. Thus, among individuals affected by HD, familiarity with and knowledge of GINA are low. The effectiveness of the legislation may be limited by this lack of knowledge.